2019
DOI: 10.1111/tri.13523
|View full text |Cite
|
Sign up to set email alerts
|

Including colon in intestinal transplantation: a focus on post‐transplant renal function – a retrospective study

Abstract: Summary Intestinal transplant recipients experience a high rate of renal complications secondary to dehydration due to increased ostomy output. It is hypothesized that inclusion of donor colon in the intestinal allograft may improve renal function in patients without functional native colon by improving fluid absorption. A single‐center retrospective study of intestinal transplant recipients compared outcomes of patients receiving en bloc colon as part an intestinal allograft (ICTx), and those not receiving co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…In various intestinal transplant scenarios, inclusion of the colon is customary, as it is linked to reduced dehydration, diarrhea rates, and heightened patient satisfaction and quality of life [29]. Studies from the University of Nebraska Medical Center indicated better posttransplant renal function in patients who received en-bloc colon in an IIT (mean delta glomerular filtration rate of −1.31 and delta blood urea nitrogen of −1.46) than patients not receiving colon (−6.54 and 17.54, respectively), with statistical significance ( P = 0.05 and P = 0.017 respectively) [33 ▪ ].…”
Section: Inclusion Of the Left Colonmentioning
confidence: 99%
“…In various intestinal transplant scenarios, inclusion of the colon is customary, as it is linked to reduced dehydration, diarrhea rates, and heightened patient satisfaction and quality of life [29]. Studies from the University of Nebraska Medical Center indicated better posttransplant renal function in patients who received en-bloc colon in an IIT (mean delta glomerular filtration rate of −1.31 and delta blood urea nitrogen of −1.46) than patients not receiving colon (−6.54 and 17.54, respectively), with statistical significance ( P = 0.05 and P = 0.017 respectively) [33 ▪ ].…”
Section: Inclusion Of the Left Colonmentioning
confidence: 99%
“…9,10 Strategies to limit malabsorptive fluid losses, such as colon-inclusive intestinal allografts, have also been recommended to augment renal recovery. 11,12 An analysis of a recent shift in our institution's practice of avoiding stoma creation at the time of transplant indicated a trend toward preservation of kidney function, although this did not reach statistical significance. 13 This study was performed to better characterize the incidence as well as further define potential risk factors for the development of CKD in intestinal transplant recipients.…”
Section: Introductionmentioning
confidence: 96%
“…These can potentially mitigate the risk of renal dysfunction. [18][19][20] T A B L E 1 International indications for intestinal transplant from the Intestinal Transplant Registry. Although previous studies highlighted these physiological advantages and improved quality of life for recipients of colonic inclusion, conflicting results have been reported regarding its impact on renal protection.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of colonic allograft encompass improved fluid absorption, residue breakdown, and stool patterns. These can potentially mitigate the risk of renal dysfunction 18–20 . Although previous studies highlighted these physiological advantages and improved quality of life for recipients of colonic inclusion, conflicting results have been reported regarding its impact on renal protection.…”
Section: Introductionmentioning
confidence: 99%